Victory's shadow conquest and governance in medieval Catalonia - Barton, Thomas W. 1976- (Cornell University Press, 2019)
"Examines how Christian forces conquered and painstakingly integrated the Muslim-ruled territory south of Barcelona over the eleventh, twelfth, and thirteenth centuries to form the remainder of the region known as Catalonia, a process that exerted lasting changes on the practice of governance throughout eastern Iberia"...